A new Ictidosuchid (Scaloposauria) from the Lystrosaurus-zone - Brink, A. S. (Bernard Price Institute for Palaeontological Research, 1965)
This paper describes a specimen recently discovered in Lystrosaurus-zone strata in the Bergville district of Natal. While a contemporary of Scaloposaurus, it has retained much of the general structure of the earlier lctidosuchidae of the Cistecephalus-zone and in a few minor respects it shows affinity with the Therocephalia, beyond the characteristics of the infra-order. The specimen consists of a good skull with lower jaw, the whole pectoral girdle with the right fore limb, and a length of anterior vertebral column with ribs; these are figured as preserved. The skull is additionally figured in three views with distortion corrected. The specimen is identified as a new genus and species, belonging to the family lctidosuchidae of the infra-order Scaloposauria, and the name Olivieria parringtoni is proposed.
None
Keywords: Ictidosuchid; Lystrosaurus-zone; South Africa